Report: Proposed new interior design scheme of Nestle Customer Centre for Nestle (Malaysia) Berhad at NO.2, Sunway Giza, Kota Damansara, 47810 Petaling Jaya, Selangor / Nor Syamimi Abdullah - Abdullah, Nor Syamimi (Faculty of Architecture, Planning and Surveying, 2011)
The final project of Diploma in Interior Design is towards students understanding in whole aspects related to the interior deisgn project’s that had beed studied from basic level to the design proposal presentation. This course acts as a comprehensive practise and design understanding exercise for students, where at this level students are given task to set up a design scheme based on research and observation correlated to some problems and issues that encounter while dealing with the design process. This final project report of Diploma in Interior Design is a report on Proposed New Interior Design Scheme of Nestle Customer Centre for Nestle Malaysia Berhad at No. 2, Sunway Giza, Kota Damansara, Petaling Jaya, Selangor. Nestle Customer Centre is an opportunity for public and Nestle’s customers as it to promote the products of nestle. Besides, people can also learn how to live a healthy lifestyle. Nestle Malaysia berhad has choosen Kota Damansara to setup the customer centre for the reason that it is a focus point at the commercial place which is nearby the main office of nestle. With the outcome of selling product and information source of Nestle Malaysia Berhad, it is a hope to make Nestle get more appreciation because always keep the responsibilities in concerning and care about the nourishments. The concept and image is also apply to both interior and exterior to appeal the centre will be able to lure more customers and visitors who were always keen in our aesthetic values in architecture. There were several researches done to succeed this accessories retail final project, amongst them are site analysis, building analysis, interview, observation and case studies. All these studies have a purpose of identifying the existing weaknesses and also attempt to solve some of the problems that appear. These investigations will be implemented in the design process with the intention to gain an attractive design and also suitable with the Nestle products.